PENGARUH CURRENT RATIO, TOTAL DEBT TO ASSETS RATIO DAN TOTAL ASSETS TURNOVER TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2009-2012 (Studi Empiris Pada Kelompok Industri Otomotif & Komponen) - Windi Puji Astuti; Muhammad Rasuli; Nur Azlina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine and determine the influence of the current ratio, total debt to assets ratio and total assets turnover to company profitability of manufacturing automotive and components industry sectors listed in Indonesia Stock Exchange (IDX) 2009-2012. The sampling method in this study using purposive sampling technique with the entire population of the manufacturing companies listed in Indonesia Stock Exchange (IDX) 2009-2012. Statistical analysis used in this study include the classical assumption and hypothesis testing using multiple linear regression. The results showed that in partial current ratio does not affect the return on assets but the total debt to assets ratio and total assets turnover significantly influence the return on assets. However, simultaneously all independent variables in this study had an influence on the profitability of companies manufacturing automotive and component industry sectors listed in Indonesia Stock Exchange (IDX) 2009-2012. The percentage of independent variables in explaining the dependent variable of 46,1% and the rest can be explained by other variables outside the model.Keywords: Current Ratio, Total Debt to Assets Ratio, Total Assets Turnover and Profitability (ROA).